PURSUIT OF TIME AND MONEY : step into radical abundance and discover the secret to a meaningful prosperous life. - Spano, Sharon L. (MORGAN JAMES Publishing, 2017)
The Pursuit of Time and Money explores the relationship between time and money and how those hidden dimensions impact perspectives and choices. The goal is to help people in business transform their relationship with time and money so they can let go of fear and scarcity and experience a more meaningful and prosperous experience of life. Sharon Spano explores the paradox of time and money from a human developmental lens that supports people in transformational change.